Combined intensive management of fertilization, tillage, and organic material mulching regulate soil bacterial communities and functional capacities by altering soil potassium and pH in a Moso bamboo forest - Zheng, Ying; Liu, Xinzhu; Cai, Yanjiang; Shao, Qingsong; Zhu, Wei; Lin, Xinchun (Frontiers in Microbiology, 2022)
Intensive management is a common practice in agricultural and forestry ecosystems to improve soil quality and crop yield by influencing nutrient supply and soil microbiota; however, the linkage between soil nutrients and bacterial community and functional capacities in intensively managed economic forests has not been well studied. In this study, we investigated the soil properties such as available potassium (AK), available nitrogen (AN), available phosphorus (AP), ammonium (NH4+), nitrate (NO3-), organic matter (OM), total nitrogen (TN), total phosphorus (TP), bacterial diversity and community composition, potential functions of rhizome roots, and soil microbiota across a chronosequence of intensively managed Moso bamboo (Phyllostachys edulis) forests. Our results demonstrated that the combined intensive managements (deep tillage, fertilization, and organic material mulching) in this study caused a significant increase in the concentrations of AK, AN, AP, NH4+, NO3-, OM, TN, and TP (P < 0.05). However, they led to a remarkable decrease in pH (P < 0.05). Such changes lowered the Shannon diversity of the soil and rhizome root microbiota but did not significantly affect the community composition and functional capacity. Soil bacterial community variation was predominantly mediated by soil total potassium (TK) (15.02%), followed by pH (11.29%) and AK (11.13%). We further observed that Nitrospirae accounted for approximately 50% of the variation in soil pH, NO3-, NH4+, and AK, indicating its importance in soil nutrient cycling, especially nitrogen cycling. Accordingly, we propose that the management-induced changes in soil parameters reshaped the bacterial community structure and keystone bacterial assemblage, leading to the differentiation of microbial functions.